Microplastic Pollution in the Inlet and Outlet Networks of Rawa Jombor Reservoir: Accumulation in Aquatic Fauna, Interactions with Heavy Metals, and Health Risk Assessment: 10.32526/ennrj/20/202100200 - Rahmayanti, Rita; Kuncoro Adji, Basith; Puspito Nugroho, Andhika (Environment and Natural Resources Journal, 2022)
Streams are regarded as a pathway for spreading microplastics from land to various aquatic systems. The contamination of streams connected to the Rawa Jombor Reservoir may increase microplastic concentrations in the reservoir. The water coming out of the reservoir carries microplastics that spread out into the stream networks around the reservoir. Heavy metals have a high affinity for microplastics, increasing metal burdens on the surface of microplastics. The transfer of microplastics along the food chain leads to the possibility of increased adverse effects on organisms, mainly top predators. This research evaluated the accumulation and characterization of microplastics in water, sediment, and aquatic fauna (zooplankton, benthos, and fish); interactions with heavy metals (Pb, Cu, Cd, and Zn); and health risk assessment. Microplastics were collected from six sampling locations. The density, type of polymers, and color of microplastics were analyzed, as well as heavy metal concentrations on the surface of microplastics and a health risk assessment. The results showed microplastic contamination at a moderate level. The accumulation of microplastics in aquatic fauna showed the same pattern as microplastics in the environment. Microplastic concentrations in aquatic fauna showed an increase through trophic transfer and indications of biomagnification. Heavy metals were adsorbed on the surface of microplastics in high concentrations. Based on the health risk assessment, microplastic contamination of fish at the inlet and outlet of the Rawa Jombor Reservoir is still safe, but further monitoring is needed because of the possible long-term health hazards that may arise.